Estudio de la resistencia A Sclerotinia sclerotiorum en líneas endocriadas de girasol - Zubrzycki, Jeremías Enrique (2015)
Sclerotinia head rot (SHR) caused by Sclerotinia sclerotiorum is one of the most important limiting factors in sunflower crop. This study aimed to identify regions of the sunflower genome associated with resistance to SHR, in order to support the development of assisted breeding strategies to accelerate the process of creating new genotypes with resistance to this disease. A population of 135 Recombinant Inbred Lines was genotyped using a collection of SNP markers associated to putative stress resistance genes. The new genetic map build has 2823.8 cM and an average density of 4.57 cM loci. We also conducted field evaluations. A total of 36 QTL distributed along 13 linkage groups were identified. The dispersion in the genome of the QTLs identified for the characters confirmed how vast and complex genetic base for sunflower resistance to SHR is. This thesis has deepened the knowledge of these regions and highlights the importance of the contribution of pointed sources in LG 10 and 15, which are presented as candidates to be analyzed in detail to advance in the identification of responsible genes that contribute to understand the complexity of resistance genetic basis.